2014
DOI: 10.1016/j.jval.2014.08.744
|View full text |Cite
|
Sign up to set email alerts
|

Guideline Adherence and Control Of Diabetes Mellitus With Co-Morbidities in a Tertiary-Care Hospital in Malaysia

Abstract: A353 p= 0.03), use of 3rd generation SU ; p= 0.002), and chronic renal disease ; p= 0.01). ConClusions: In conclusion, multiple factors, including efficacy and hypoglycemia, are associated with discontinuation of SU treatment after insulin initiation.objeCtives: Sulfonylurea (SU) may be discontinued or down-titrated due to hypoglycemia. Hypoglycemia may be more concerning for patients not receiving aggressive efficacy-driven treatment such as the dual-therapy of SU and insulin. A retrospective cohort study usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…[1135] These guidelines recommend prescribing of an Angiotensin Converting Enzyme Inhibitor or Angiotensin Receptor Blocker unless contraindicated, as the preferred antihypertensive in patients with diabetes mellitus in comorbidity of hypertension. [3738]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1135] These guidelines recommend prescribing of an Angiotensin Converting Enzyme Inhibitor or Angiotensin Receptor Blocker unless contraindicated, as the preferred antihypertensive in patients with diabetes mellitus in comorbidity of hypertension. [3738]…”
Section: Discussionmentioning
confidence: 99%
“…Although the chances of development of diabetes with statin use are reported,[3839] many meta-analyses on randomized trials reported the advantages of statins to decrease the CV risks. [163740]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the literature, it has been proven that the teamwork of physicians and pharmacists resulted in improved glycemic control in diabetic patients (Iqbal et al, 2014;. In Malaysia, pharmacists are directly working together with physicians in all tertiary hospitals by Diabetes Medication Therapy Adherence Clinic (DMTAC) program.…”
Section: Introductionmentioning
confidence: 99%
“…Socioeconomic factors of parents are predictors in influencing child healthcare and their decision making about their children health and wellbeing and provision of all the facilities are solely based on their socioeconomic status 37,38 . A study based on the predictors affecting the childhood immunization shows that timely process of immunization is affected by the parent's income and their employment status which can be judged as defining factors 39 .…”
Section: Discussionmentioning
confidence: 99%